USM IPS CELEBRATES THE SUCCESS OF POSTGRADUATE STUDENTS - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 31 December 2015 – Universiti Sains Malaysia (USM) Institute of Postgraduate Studies (IPS) celebrated the success of postgraduate students who excelled in various fields at the Majlis Persada Kencana (MPK) 2015 ceremony here today.